(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
The experiment was conducted in the Aman season of 2016, at Bangladesh Rice Research Institute farm under the Agro Ecological Zone (AEZ 28) Modhupur Tract. The CN6 is a high spikelet bearing advanced line of rice but low in spikelet fertility. Micronutrient management was examined to increase its spikelet fertility. Five treatments were used in this experiment. The treatments were as follows: T1= BRRI recommended fertilizer dose + MgO @ 0.05%, T2 = BRRI recommended fertilizer dose + 60 g MoP + 60 g elemental S (80% wp) + 20 g ZnSO4, T3 = BRRI recommended fertilizer dose + Boron @ 5ppm, T4= BRRI recommended fertilizer dose + Copper @ 5ppm) and T5 = BRRI recommended fertilizer dose alone. The experiment was conducted in Randomized Complete Block design with three replications. The results indicated that Treatment T3 (BRRI recommended fertilizer dose + Boron @ 5ppm) produced the more number of grains per panicle with an average of 194 which is higher number of grains per panicle over the control treatment T5 (BRRI recommended fertilization alone). Treatment T4 produced the highest number of 1000- grains weight (17.9 g). However, highest grain yield was recorded in the treatment T4 with an average of 3.94 t ha-1 compare to the control treatment T5 (BRRI recommended fertilization alone). Second highest grain yield (3.70 t ha-1) was found under the treatment T2 followed by T1 (3.57 t ha-1) and T3 (3.57 t ha-1). The lowest grain yield was recorded in the control treatment T5 (BRRI recommended fertilization alone). Taken together, our results suggested that micronutrient management, especially copper and zinc, improved the spikelet fertility of an advanced line CN6 resulting higher yield. Res. Agric., Livest. Fish.7(1): 51-59, April 2020